Correlation Between Bruto Domestic Products (Gdp) With Duty Schools - Hardianto Wibowo; Daroe Iswatiningsih; Wildan Suharso; Fachrunnisa Firdausi (IAES Indonesia Section, 2018)
This study aims to analyze the linkage of dropout rates with Gross Domestic Product (GDP). The data source of this research is the Central Bureau of Statistics (BPS), with data acquisition of GDP and drop out rate of elementary, junior and senior high school year 2008 until 2011. Data obtained through quantitative approach with secondary data source. The connectedness value between school dropout and GDP at primary level was 0.7294 in 2008, 0.7225 in the year of 2009, 0.4393 in 2010 and 0.3878 in 2011. While the relationship between the number of dropouts and GDP of junior high school level is 0.6095 in 2008, 0.6238 in 2009, 0.3605 in 2010 and 0.2467 in 2011. while the relationship between the drop out rate and GDP of the SMA level was 0.6061 in 2008, 0.5965 at in 2009, 0.5321 in 2010 and 0.2606 in 2011.